From Magic to Algorithms: Reimagining Prospero in Atwood’s Hag-Seed - Paudel, Bhagabat (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2026)
This paper explores Margaret Atwood’s Hag-Seed reimagination of Shakespeare’s The Tempest through the lens of digital surveillance and information control, a new form of revenge in the present. Felix’s method of observation, manipulation, and behavioral regulation invites digital domination called data colonialism. Using qualitative textual analysis, the novel is analyzed using the theoretical frameworks of digital humanism, surveillance capitalism (Zuboff), and data colonialism (Couldry and Mejías). The evidence shows that Felix’s deployment of cameras, recordings, and algorithmic monitoring illustrates a modern system of data extraction that incubates human behavior for controlling and economic motives. The prison theatre is programmed as a controlling microcosm in which inmates are disciplined, programmed, mirroring data control practices. Prospero’s magical authority is now transformed for Felix into technological governance, a shifting locus of power from physical to informational control. Thus, Hag-Seed demonstrates how modern technologies, surveillance, and exploitation are new means of colonization. Digital systems create new and widespread threats to human autonomy.